CORO1C is Associated With Poor Prognosis and Promotes Metastasis Through PI3K/AKT Pathway in Colorectal Cancer - Wang, Zongxia; Jia, Lizhou; sun, Yushu; Li, Chunli; Zhang, Lingli; Wang, Xiangcheng; Chen, Hao (Frontiers in Molecular Biosciences, 2021)
Coronin-like actin-binding protein 1C (CORO1C) is involved in cancer metastasis. However, the expression and function of CORO1C in colorectal cancer (CRC) remains unclear. Immunoprecipitation and mass spectrometry identified proteins interacting with trophoblast cell surface protein 2 (Trop2). Tissue microarrays and immunohistochemistry were performed to detect the expression of CORO1C protein and define its prognostic value in CRC. The correlation between CORO1C expression and clinical characteristics was analyzed. The functions of CORO1C in CRC were determined by CCK-8 proliferation, colony formation, transwell migration/invasion, and in vivo assays. The underlying mechanism was identified by bioinformatics analysis and Western blot. We found that CORO1C interacted with Trop2 and highly related to CRC metastasis. The CORO1C expression in CRC tissues was higher than that in paracarcinoma tissues. The overexpression of CORO1C was associated with histological type, lymph node metastasis, distant metastasis, AJCC stage, venous invasion, and perineural invasion. CRC patients with high CORO1C expression were associated with poor prognosis. The downregulation of CORO1C showed an anti-cancer influence on CRC cells in clone formation, cell proliferation, migration, and invasion, and decelerated xenograft tumor growth in nude mice. CORO1C knockdown significantly decreased the expression of fibronectin, vimentin, p-PI3K and p-AKT, and increased E-cadherin expression. Thus, this study indicates that the stimulative role of CORO1C in CRC metastasis was confirmed by activating PI3K/AKT signaling pathway. Thus, CORO1C could be a valuable prognostic biomarker in CRC patients.